Interpreting digital traces:- 8 foundational pillars to support the formation of opinion in digital forensics - Horsman, Graeme (Elsevier, 2024)
The field of digital forensics (DF) is facing increasing scrutiny of the quality of the work it produces. Fundamental to it is the need for its practitioners to be able to accurately determine the meaning of potentially relevant digital traces found during an examination of a device. As the reliance on digital evidence continues to grow, so does the importance of digital trace-interpretation. It is therefore imperative that this task is conducted robustly, where this work describes ‘eight pillars’ that should underpin how a practitioner has gone about interpreting any given digital trace.
Keywords: Digital Forensics; Digital Trace; Investigation; Interpretation